Long-term outcomes of modified Berlin–Frankfurt–Münster-90 regimen in adults with T-lymphoblastic lymphoma: a single-center experience. Issue 8 (August 2014) - Wang, Kefeng; Chen, Xiaoqin; Wuxiao, Zhijun; Wang, Zhihui; Sun, Xiaofei; Zeng, Zijun; Li, Su; Xia, Zhong-jun
Abstract The standard treatment for adult T-Lymphoblastic lymphoma (T-LBL) has not been defined. This study was to analyze the efficiency of modified BFM-NHL-90 regimen in 36 adult patients with newly diagnosed T-LBL at the Sun Yat-Sen cancer center between August 2000 and December 2010. After the induction protocols, 34/36 (94%) of the patients achieved complete remission or unconfirmed complete remission. At the median follow-up of 36 months, 13 patients relapsed, but no relapses were observed in the CNS. The 3-year overall survival and 3-year event-free survival rates were 66.9% and 65.4%, respectively. Patients of female gender with hepatomegaly and hemoglobin less than 120 g/L, and the time interval exceeding 38 days between induction 1a and 1b, had inferior EFS and OS. The results was comparable to the previous regimens and the regimen could prevent CNS relapse with 4 high-dose MTX every 3 months during the maintenance phase.